Case Report: Near-complete resolution of nail psoriasis with upadacitinib in a pediatric patient - Yulin Huang; Sijian Wen (Frontiers in Immunology, 2026)
Nail psoriasis (NP) is refractory in children, causing punctate pits, onycholysis, subungual hyperkeratosis and discoloration, impairing quality of life. We report a 14-year-old boy with 4-year NP, all fingernails involved with no cutaneous lesion, and unresponsive to traditional therapy. After 20-week oral upadacitinib, all nail lesions achieved near-complete resolution with only minimal residual nail changes, and no treatment-related adverse events. This suggests that upadacitinib demonstrates favorable efficacy and safety for pediatric refractory NP, large-scale prospective clinical investigation are warranted to validate our findings.